2023
DOI: 10.1177/10668969231157317
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Morphological Features of Clear Cell Renal Cell Carcinoma With PBRM1, SETD2, BAP1, or KDM5C Mutations

Abstract: The last decade has seen great advances in genomic profiling and prognosis-associated factors of clear cell renal cell carcinoma (RCC), the most common entity in kidney cancer. Following VHL, PBRM1, SETD2, BAP1, and KDM5C have been validated as the most common co-occurring gene mutations in clear cell RCC by multicenter studies. However, the morphological features of clear cell RCC with co-occurring gene mutations remain unclear. In this study, we presented 20 clear cell RCCs that underwent next-generation seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…PBRM1 protein is a subunit of the PBAF chromatin remodeling ATP-dependent complex necessary for ligand-dependent transcriptional activation by nuclear hormone receptors; it can act either as a tumor suppressor, for example in ccRCC, or oncogene, for example in prostate cancer. It should be stressed that following VHL , PBRM1 , SETD2 , BAP1 , and KDM5C have been validated as common co-occurring gene mutations in ccRCC in multicenter studies [ 60 ]. In this latter study, results suggested that PBRM1 mutation does not correlate with decreased survival, whereas BAP1 mutation seemed to predict poor outcome.…”
Section: Biological Biomarkers Of Icis Responsementioning
confidence: 99%
“…PBRM1 protein is a subunit of the PBAF chromatin remodeling ATP-dependent complex necessary for ligand-dependent transcriptional activation by nuclear hormone receptors; it can act either as a tumor suppressor, for example in ccRCC, or oncogene, for example in prostate cancer. It should be stressed that following VHL , PBRM1 , SETD2 , BAP1 , and KDM5C have been validated as common co-occurring gene mutations in ccRCC in multicenter studies [ 60 ]. In this latter study, results suggested that PBRM1 mutation does not correlate with decreased survival, whereas BAP1 mutation seemed to predict poor outcome.…”
Section: Biological Biomarkers Of Icis Responsementioning
confidence: 99%
“…Further frequently altered genes in ccRCC are chromatin-modifying genes: polybromo-1 (PBRM1), BRCA1 associated protein 1 (PAB1), SET domain containing 2 histone-lysine Nmethytransferase (SETD2), located on the same 3p chromosomal region [82][83][84], and less frequently, lysine demethylase 5C (KDM5C) located on the X chromosome [85] and telomerase reverse transcriptase (TERT) promoter located on chromosome 5p [86,87]. The frequency of detectable VHL defects is estimated to be up to 90% [58,86,[88][89][90]. In contrast, the incidence of the other altered driver genes is significantly lower: PBRM1 52.6-26.4%, SETD2 35-7.6%, BAP1 31-7.5%, KDM5C 16-3.8%, TERT 14-12.2% and mTor 13-5.7% [58,84,86,88,89,[91][92][93][94].…”
Section: Genetic Characteristics and Peculiarities Of The Ispmrcc 21 ...mentioning
confidence: 99%
“…The frequency of detectable VHL defects is estimated to be up to 90% [58,86,[88][89][90]. In contrast, the incidence of the other altered driver genes is significantly lower: PBRM1 52.6-26.4%, SETD2 35-7.6%, BAP1 31-7.5%, KDM5C 16-3.8%, TERT 14-12.2% and mTor 13-5.7% [58,84,86,88,89,[91][92][93][94]. It was soon recognised that these gene alterations are associated with a different tumour biology, and thus, have an influence on the course of the disease and the outcome [90,95].…”
Section: Genetic Characteristics and Peculiarities Of The Ispmrcc 21 ...mentioning
confidence: 99%
See 2 more Smart Citations